1985
DOI: 10.1037/0022-0663.77.4.383
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the semantic similarity of items on student ratings of instructors.

Abstract: Factor analysis of student ratings of teacher effectiveness may reveal more about the semantic similarity of items than it does about actual covariation in instructor behavior. To test this hypothesis, 28 graduate students were asked to rate several hypothetical instructor profiles, constructed by systematically manipulating information about the instructors' classroom behaviors. Factor analyses of the student ratings were performed before and after all behavioral information in the instructor profiles had bee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
39
0
1

Year Published

1989
1989
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(40 citation statements)
references
References 30 publications
0
39
0
1
Order By: Relevance
“…Thus, the structure of personality factors could be influenced by what is thought to go with what rather than what actually goes with what. Cadwell and Jenkins (1985) present a clear example of the possible effect of systematic distortion on student ratings of teaching:…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the structure of personality factors could be influenced by what is thought to go with what rather than what actually goes with what. Cadwell and Jenkins (1985) present a clear example of the possible effect of systematic distortion on student ratings of teaching:…”
mentioning
confidence: 99%
“…The effects of systematic distortion or conceptual association bias have been studied in several different areas, including general personality assessment (Berman and Kenny, 1976;Block, Weiss, and Thorne, 1979;Hamilton and Rose, 1980;King and Koehler, 2000;Paunonen and Jackson, 1979;Riemann and Angleitner, 1993;Shweder, 1975), clinical applications (Chadwick and Taylor, 2000;Chapman, 1967, 1969;Dollinger, Greening, and Radtke, 2001;Shweder, 1977;Shweder and D'Andrade, 1980), job performance evaluations (Cooper, 1981;Dewhirst and Berman, 1978;Kozlowski, Kirsch, and Chao, 1986;Vonk, 1998), and student ratings of instructors (Cadwell and Jenkins, 1985;Lodzinski, 1991;Lodzinski, Schneider, and Murray, 1991;Whitely and Doyle, 1976). Unfortunately, there appears to be a lack of consensus on the extent to which covariance in ratings of dimensions of personality or performance is biased by systematic distortion.…”
mentioning
confidence: 99%
“…In many cases, attitude-based rating scales produced good reliability and validity. However, some researchers argued that such results could depend on the semantic similarity of items more than on variations in real behavior (e.g., Cadwell & Jenkins, 1985), or that performance judgements are influenced not only by reality, but also by implicit standards of effective behavior (e.g., Kishor, 1995). Additionally, in social research, some researchers found evidence for an "attitude-behavior gap" which means that sometimes or even often people do not behave according to their attitudes, values, or intentions (e.g., Greve, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Hypothetical ratee profiles limited the amount of detail that could be included, but were judged to be suitable because it is a procedure that allows control over the amount of information. Moreover, the use of hypothetical profiles was justified because in a real situation students often evaluate on general impressions and not on specific details (Cadwell & Jenkins, 1985).…”
Section: Performance Rating Taskmentioning
confidence: 99%
“…This choice was based on the wide use of policy-capturing analysis in previous related research (Cadwell & Jenkins, 1985;Zedeck & Cascio, 1982;Zedeck & Kafry, 1977), and in various other areas where information utilization has been of interest (Borko & Cadwell, 1982;Cadwel & Jenkins, 1986).…”
Section: Desertmentioning
confidence: 99%